Leaf-cutter ants engineer large nitrous oxide hot spots in tropical forests. Issue 1894 (16th January 2019) - Soper, Fiona M.; Sullivan, Benjamin W.; Osborne, Brooke B.; Shaw, Alanna N.; Philippot, Laurent; Cleveland, Cory C.
Abstract : Though tropical forest ecosystems are among the largest natural sources of the potent greenhouse gas nitrous oxide (N2 O), the spatial distribution of emissions across landscapes is often poorly resolved. Leaf cutter ants (LCA; Atta and Acromyrmex, Myrmicinae) are dominant herbivores throughout Central and South America, and influence multiple aspects of forest structure and function. In particular, their foraging creates spatial heterogeneity by concentrating large quantities of organic matter (including nitrogen, N) from the surrounding canopy into their colonies, and ultimately into colony refuse dumps. Here, we demonstrate that refuse piles created by LCA species Atta colombica in tropical rainforests of Costa Rica provide ideal conditions for extremely high rates of N2 O production (high microbial biomass, potential denitrification enzyme activity, N content and anoxia) and may represent an unappreciated source of heterogeneity in tropical forest N2 O emissions. Average instantaneous refuse pile N2 O fluxes surpassed background emissions by more than three orders of magnitude (in some cases exceeding 80 000 µg N2 O-N m −2 h −1 ) and generating fluxes comparable to or greater than those produced by engineered systems such as wastewater treatment tanks. Refuse-concentrating Atta species are ubiquitous in tropical forests, pastures and production ecosystems, and increase density strongly in response to disturbance. As such, LCA colonies may represent an unrecognized greenhouse gas point source throughout the Neotropics.